Fused Filament Fabrication of Piezoresistive Carbon Nanotubes Nanocomposites for Strain Monitoring - Dul, Sithiprumnea; Pegoretti, Alessandro; Fambri, Luca (Frontiers in Materials, 2020)
Conductive carbon nanotubes (CNT)/acrylonitrile butadiene styrene (ABS) nanocomposites parts were easily and successfully manufactured by fused filament fabrication (FFF) starting from composite filaments properly extruded at a laboratory scale. Specific specimens for strain monitoring application were properly evaluated in both short term and long term mechanical testing. In particular, samples of ABS filled with 6 wt% of CNT were additively manufactured in two different infill patterns: HC (0°/0°) and H45 (−45°/+45°). The piezoresistivity behaviour was investigated under various loading conditions such as ramp tensile tests at different rate and extension, and also creep and cyclic loading at room temperature. Experimental work revealed that the resistance changes in the conductive samples were properly detectable during stress or strain modification, as consequence of damage and/or reassembling of the percolation network. The measurement of the gauge factor in various testing conditions evidenced an initial higher sensitivity of the 3D-built parts within H45 pattern in comparison to the correspondent HC counterparts. The CNT conductive network path in the investigated samples seems to be reformed during creep and cycling experiments, showing a progressive reduction of gauge factor that seems to stabilize at about 2.5 for both HC and H45 samples after long term testing. These findings suggest that conductive CNT/ABS nanocomposites at 6 wt% of loading can be successfully processed by FFF to produce stable strain sensors in the range -25° and +60°C, as confirmed by the constancy of resistivity at these temperatures.